O seguro prestamista: uma análise sobre a natureza jurídica e a importância socioeconômica - Gonçalves, Tiago Moraes (2012)
The purpose of this Master's dissertation is to analyze a type of insurance contract ¬ that is becoming increasingly important in Brazil and the world, and that is sti11little 'explored by the doctrine and mistakenly interpreted by case law: the Consumer credit insurance. This type of insurance guarantees the payment of a debt of the insured person, or part thereof, in case of the occurrence of an event covered by the policy agreed upon. The consumer credit insurance is developed within the scope ofthe Consumer Society and one ofits focal points is precisely the credit, assisting in maintaining the status quo of the social structure, by making possible a significant reduction in the risk of default in the concession of credit, thus fulfilling, an important sgcial function. The analysis therefore is not Rossible, without a theoretical overflight on the socioeconomic reality that justified the creation and development of the consumer credit insurance. Furthermore, with the aim of establishing the foundations for the interpretation of this contract, the work focuses on an analysis of the insurance transaction, addressing key issues inc1udingtransindividual interests, the entrepreneurship of the insurance activity, the commutativeness of the contract and the; interest as a legalIy protected asset, as welI as a brief digression on the legal framework of the insurance contracts and legal matters conceming their legal c1assification. The work finalIy analyzes the consumer contract insurance itself, exploring all the components, coverage provided, interests involved, the practices of the insurance market in the pre-contractual stage, the completion and execution to, at the end, offer a new insight into their legal nature, aiming to contribute to the doctrine and national jurisprudence for a better understanding of this contractual model.